Dementia and inappropriate sexual behavior: What we know and what we need to know - Josep Fabà; Feliciano Villar (Kairós Gerontologia, 2012)
Traditionally, there has been no place for sexuality in older age. However, research has shown that sexuality plays an important role in older people’s life, even in situations such as dementia. The goal of the article is to review the scientific literature regarding the inappropriate sexual behavior that these kind of patients might present. In order to do so, we will firstly address the definition of inappropriate sexual behavior or, more precisely, its multiple definitions. After that, we will deal with other issues such as its prevalence, factors that can cause its appearance, its consequences and some of the available therapeutic options. Finally, in the last section some recommendations for future research will be provided, such as the need to clarify the concept of inappropriate sexual behavior, to find more efficient ways to address this problem, and the desirability of considering sexuality as a human dimension with a high potential for adaptation in old age.